Acoustic fluid–structure study of 2D cavity with composite curved flexible walls using graphene platelets reinforcement by higher-order finite element approach. (15th September 2021) - Pitchaimani, Jeyaraj; Gupta, Prateek; Rajamohan, Vasudevan; Polit, Olivier; Manickam, Ganapathi
Highlights: Applied FEA for acousto-structure interaction of 2D cavity with flexible walls. Studied strong/weak fluid coupling of flexible cavity with curve beam on top. Examined structural, coupled frequencies and SPL for rigid/flexible wall cavities. Investigated GPL reinforced fluid-filled flexible cavity walls for SPL response. Abstract: In the present study, acousto-vibration analysis of 2D fluid-filled cavities/tanks having flat and curved flexible walls is made using a trigonometric function based shear deformable theory and the Helmholtz wave model for fluid domain. The governing equation formed here is solved through higher-order finite element approach. The walls are modeled by C 1 continuous 3-noded beam element and the fluid is idealized using an eight-noded quadrilateral element. Structural and coupled frequencies are evaluated for fluid-filled cavities with rigid/flexible vertical walls along with flat/curved beam on top. The sound pressure level is also predicted in the fluid domain due to a steady-state mechanical harmonic load on the top of the cavity. This investigation is conducted for metallic cavities and then extended to graphene platelets reinforced cavity. The effect of degree of fluid–structure coupling is examined assuming different fluid domains. Considering a wide range of cavity geometry and material parameters such as thickness ratio, curved beam angle, graded porosity and graphene platelets, porosity coefficient, loading of GPL, fluid medium, a comprehensive investigation is depicted to highlight their impacts on vibro-acoustic nature of fluid-filled cavities. It is observed that the dynamic characteristics of rigid and flexible wall cavities are significantly different from each other.